Analysis of Microplastics in Human Feces Reveals a Correlation between Fecal Microplastics and Inflammatory Bowel Disease Status - Yan, Zehua; Liu, Yafei; Zhang, Ting; Zhang, Faming; Ren, Hongqiang; Zhang, Yan (Environmental science & technology, 2022)
Human ingestion of microplastics (MPs) is inevitable due to the ubiquity of MPs in various foods and drinking water. Whether the ingestion of MPs poses a substantial risk to human health is far from understood. Here, by analyzing the characteristics of MPs in the feces of patients with inflammatory bowel disease (IBD) and healthy people, for the first time, we found that the fecal MP concentration in IBD patients (41.8 items/g dm) was significantly higher than that in healthy people (28.0 items/g dm). In total, 15 types of MPs were detected in feces, with poly(ethylene terephthalate) (22.3-34.0%) and polyamide (8.9-12.4%) being dominant, and their primary shapes were sheets and fibers, respectively. We present evidence indicating that a positive correlation exists between the concentration of fecal MPs and the severity of IBD. Combining a questionnaire survey and the characteristics of fecal MPs, we conclude that the plastic packaging of drinking water and food and dust exposure are important sources of human exposure to MPs. Furthermore, the positive correlation between fecal MPs and IBD status suggests that MP exposure may be related to the disease process or that IBD exacerbates the retention of MPs. The relative mechanisms deserve further studies. Our results also highlight that fecal MPs are useful for assessing human MP exposure and potential health risks.